JUDICIAL TRENDS IN ENVIRONMENTAL LAW WITH SPECIAL REFERENCE TO ENVIRONMENT PROTECTION, ACT 1986 - Nazneen; Jeet, Shobana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper explores the judicial trends in environmental law with a particular focus on environmental protection as observed in 1986. The year marked a pivotal moment in the evolution of environmental jurisprudence, reflecting a significant shift in how courts approached environmental issues. Key judicial developments from 1986 reveal an increased recognition of environmental rights and the judiciary’s growing role in enforcing environmental regulations. This period saw a rise in landmark cases that emphasized the importance of environmental sustainability and the need for rigorous legal mechanisms to address pollution and ecological harm. The paper reviews notable judgments from 1986, analysing their impact on environmental law and policy, and examines how these judicial trends contributed to the strengthening of environmental protection frameworks. The analysis underscores the critical role of the judiciary in shaping environmental governance and highlights the continuing relevance of these early trends in contemporary environmental law.